Tourism Village Development as An Effort to Improve Community Welfare in Sodong Village - Varya Puspita Sari; Fatikhatus Sania; Ahmad Hidayatullah (Prosperity: Journal of Society and Empowerment, 2023)
Sodong Village is located in the highlands of Batang Regency. The area around Sodong has many unique cultures and traditions. For this reason, it is necessary to develop a tourist village by holding activities to support tourism potential, where these activities will emphasize the elements of experience and interaction between tourists and the local community; for this reason, the existence of potential development in the village is used for the welfare of the Sodong people. The research location was in the highlands, specifically in Sodong Village, Wonotunggal sub-district, Kab. Stem. The research method used is descriptive analytics. The descriptive method is a method that has the function of explaining general things about an object. The stages carried out were observation, interviews, documentation, and data collection. The results of the study illustrate that the development of the potential of the Sodong tourism village can prosper the community, namely by implementing the 4A components (Attraction, amenities, Ancillary, and Accessibility). Therefore, the people of Sodong can prevent and reduce the emphasis on the rate of urbanization by opening up jobs from tourism development activities.